Lateral Impact Response of Concrete-Filled Square Steel Tubes with Local Defects - Yulin Wang; Shan Gao; Youchun Xu; Fangyi Li (Buildings, 2022)
A numerical model of 84 high-strength concrete-filled square steel tubular columns (HSCFST) with local defects is developed using ABAQUS. The effects of parameters such as crack angle, crack length, impact surface and impact energy on the impact resistance of HSCFST columns are considered. The results show that under the effect of local corrosion, a model with horizontal cracks will show the phenomenon of crack closure when subjected to the front impact. The impact force platform value is mainly affected by the impact surface, followed by the crack angle, while the increase of the crack length mainly has a greater effect on the model of the rear impact. The impact resistance of the front impact model is better than that of the side and rear impact models. Increasing the crack length and decreasing the crack angle will increase the mid-span deflection of the model, and the mid-span deflection of the front impact model is smaller than that of the side and rear impact models. The energy absorption ratio of the model is proportional to the increase of the crack length and inversely proportional to the increase of the crack angle. Decreasing the crack angle will reduce the increase coefficient (Rd) of the dynamic flexural capacity of the model. A practical calculation method for the increased coefficient of the dynamic flexural capacity of HSCFST columns under local corrosion is proposed.